Peran KPK Dalam Pemberantasan Korupsi Di Indonesia - Nurhaliza Trie Anna Dewi (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Corruption is a serious problem that hampers economic growth and weakens government institutions in Indonesia. The Corruption Eradication Commission (KPK) was established as an independent institution to eradicate corruption with various strategies, including prevention, investigation, and prosecution. This study aims to analyze the role of the KPK in eradicating corruption in Indonesia with a descriptive qualitative approach based on literature study and secondary data analysis. The results show that although the KPK has successfully handled various major corruption cases, the revision of the KPK Law in 2019 weakened the independence of this institution, thus affecting its effectiveness. The recommendations of this study emphasize the importance of strengthening the KPK's authority, increasing transparency, and public participation in supporting corruption eradication efforts.